Profit shifting and 'aggressive' tax planning by multinational firms: Issues and options for reform - Clemens Fuest; Christoph Spengel; Katharina Finke; Jost Heckemeyer; Hannah Nusser (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
This paper discusses the issue of profit shifting and 'aggressive' tax planning by multinational firms. The paper makes two contributions. Firstly, we provide some background information to the debate by giving a brief overview over existing empirical studies on profit shifting and by describing arrangements for IP-based profit shifting which are used by the companies currently accused of avoiding taxes. We then show that preventing this type of tax avoidance is, in principle, straightforward. Secondly, we argue that, in the short term, policy makers should focus on extending withholding taxes in an internationally coordinated way. Other measures which are currently being discussed, in particular unilateral measures like limitations on interest and license deduction, fundamental reforms of the international tax system and country-by-country reporting, are either economically harmful or need to be elaborated much further before their introduction can be considered.
urn:nbn:de:bsz:180-madoc-339460
Keywords: H20; H25; F23; K34; 330; tax avoidance; profit shifting; multinational firms; intellectual property; tax policy; tax reform